Assessing the suitability and dynamics of three medicinal Sambucus species in China under current and future climate scenarios - Luo, Weixue; Han, Shunxin; Yu, Ting; Wang, Peng; Ma, Yuxuan; Wan, Maji; Liu, Jinchun; Li, Zongfeng; Tao, Jianping (Frontiers in Plant Science, 2023)
Climate change exerts profound influences on the ecological environments on a global scale, leading to habitat destruction and altering distribution patterns for numerous plant species. Traditional Chinese medicinal plants, such as those belonging to the Sambucus genus, have been extensively utilized for several centuries to treat fractures, rheumatism, and inflammation. However, our understanding of their geographic distribution and climatic adaptation within China still needs to be improved. In this study, we screened the optimal predictive model (random forest model) to predict the potential suitable distribution of three Sambucus species (Sambucus adnata, Sambucus javanica, and Sambucus williamsii) across China under both current and future climate scenarios.Moreover, we identified key climate factors that influence their potential distributions.Our findings revealed that S. adnata and S. javanica are predominantly shaped by temperature seasonality and mean diurnal range, respectively, whereas S. williamsii is significantly affected by the precipitation of the wettest month. Currently, S. williamsii is primarily distributed in north and central south China (covering 9.57 × 10 5 km 2 ), S. javanica is prevalent in the south and east regions (covering 6.41×10 5 km 2 ), and S. adnata predominantly thrives in the southwest China (covering 1.99×10 5 km 2 ). Under future climate change scenarios, it is anticipated that S. adnata may migrate to higher latitudes while S. javanica may shift to lower latitudes. However, potentially suitable areas for S. williamsii may contract under certain scenarios for the years 2050 and 2090, with an expansion trend under the SSP585 scenario for the year 2090. Our study emphasizes the importance of climatic variables in influencing the potential geographic distribution of Sambucus species. These findings provide valuable theoretical insights for the preservation, cultivation, and utilization of Sambucus medicinal plant resources in the context of ongoing climate change.